Evaluation of polymorphisms at the 3´ UTR SLC11A1 gene microsatellites and their associations with the outcome of Brucella abortus infection in Bos taurus cattle - Hasenauer, Flavia Carolina; Caffaro, María Eugenia; Poli, Mario Andres; Rossetti, Carlos Alberto (Ediciones INTA, 2022)
In ruminants, polymorphisms in microsatellites at 3´untranslated region (3´ UTR) of the SLC11A1 gene were associated with natural resistance to Brucella spp. and Mycobacterium spp. infection, but its relevance to prevent brucellosis is controversial in cattle. The aim of this study was to re-evaluate the role of these polymorphisms in the outcome of Brucella abortus infection in European bovine breeds. Initially, the presence or absence of specific antibodies against Brucella abortus in beef (n=74) or dairy (n=69) Bos taurus cattle at high risk of natural Brucella infection was used to identify susceptible (cases, infected) or resistant (control, non-infected) animals. Then, innate resistance to Brucella infection was evaluated in B. taurus peripheral blood monocyte-derived macrophages (MDMs) challenged with the pathogen. Finally, a bioinformatics analysis of the 3′ UTR of the SLC11A1 gene was performed to evaluate its putative functional impact on gene regulation. Fifty four (54) brucellosis positive and 89 brucellosis negative animals were genotyped for both microsatellites by multiplex PCR-capillary electrophoresis. Our results showed that the homozygous genotypes 159 and 175 for Ms1 and Ms2 respectively, previously defined as “resistant” genotypes, were the most frequent among the animal population. Independently, no association was detected between these or other polymorphisms and the absence or presence of humoral immune response against brucellosis. Moreover, no association was observed between the resistant genotype with the restricted B. abortus-intracellular growth phenotype in MDMs. In silico analysis of 3′ UTR sequence predicted two canonical binding sites for transcriptional regulatory elements belonging to TEF-1 and SMAD families, but most importantly, the secondary structure of the 3’UTR remains unchanged regardless of the length of the microsatellites. Taken together, these results show no evidence of an association between the 3’UTR SLC11A1 polymorphisms and natural resistance against brucellosis in cattle.